Performance Evaluation of Image Transmission over Physical Layer Of IEEE 802.16d with Antenna Diversity Scheme - Nayak, Apoorva; Sharma, Rahul (International Journal of Computer Sciences and Engineering, 2014)
The image is becomes a fundamental data for communication which needs high data rate for transmission. The image transmission over wireless communication system suffers from distortion due to the adverse effect of channel. In Multiple-Input Multiple-Output based wireless system is a promising high data rate interface technology and wireless multipath fading. In a method based on Space-Time Block Coding (STBC) with Multiple-Input Multiple-Output set-up for use in wireless channels. A comparison is made between the diversity gain of MIMO systems in terms of BER for High QAM modulation scheme. In this paper, performance of WIMAX physical layer is simulated and bit error rate (BER) performance is observed. In BER level is depend on the modulation type, then SNR value and channel behavior. The Modulation schemes that we have used in this paper are QPSK, QAM-8 and QAM-16 which further improved using MIMO technique. The poor bit error ratio (BER) at receiver also calculated as poor PSNR with received image. The results have been shown in the paper for the simulation over various diversity.